Analisis Metode Elektrokoagulasi dalam Penurunan Besi, Mangan dan Total Suspended Solid pada Air Gambut - Enaya Primsa Br Perangin Angin; Gusri , Lailal; Syukria Putra, Tri; Abdul Manab (Jurnal Serambi Engineering, 2025)
Peat water originates from the incomplete decomposition of plant material in low-lying and swampy areas. It has properties that can harm human health, such as high acidity and a reddish-brown colour. It also contains dissolved metals, such as iron and manganese, and has a high organic content. The aim of this study is to treat peat water using the electrocoagulation method in order to improve its quality in line with clean water quality standards. Electrocoagulation uses electrical energy to coagulate solids and reduce the content of dissolved metals. This study was conducted using peat water from Pandan Jaya Village in the Geragai District of the East Tanjung Jabung Regency in the Jambi Province. Electrical voltages of 10, 20 and 30 volts were used, as well as contact times of 60, 120 and 180 minutes. After electrocoagulation treatment, the results showed that iron levels decreased by 98% (from 4.28 mg/L to 0.0871 mg/L), manganese by 87.6% (from 0.2667 mg/L to 0.0330 mg/L), total suspended solids by 92.2% (from 24.43 mg/L to 1.9 mg/L), and pH by 100% (from 3.10 to 7.41). These results suggest that electrocoagulation is an effective method of reducing peat water pollution and improving its quality to meet national clean water standards.